Technologies of critique - Thayer, Willy (Fordham University Press, 2020)
Technologies of Critique elaborates a critical practice that eludes critique's capture by institutional and market logics. Building on Chile's history of dissident art and its entangling of politics and aesthetics, Thayer engages continental philosophical traditions, to help pinpoint the technologies and media through which art intervenes critically in socio-political life.
Keywords: Criticism -- History -- 20th century.; Art and society.; Art criticism.; Art criticism -- Political aspects.; Art -- Political aspects.; Critique -- Histoire -- 20e siècle.; Art et société.; Critique d'art.; Art -- Aspect politique.; Critique d'art -- Aspect politique.; art criticism.; political art.; PHILOSOPHY -- Movements -- Critical Theory.; Criticism; Art and society; Art criticism; Art criticism -- Political aspects; Art -- Political aspects; 1900-1999; History; Literary criticism.; Critiques littéraires.